The Application Glodon Software During Pre-Contract Stage - Nurdiana Azmi; Ting Li Yi; Mazianah Rahmat; Nurhayatul Khursniah Hasim; Toh Tien Choon; Mohd Hilmi Izwan Abd Rahim; Rubiah Md Zan (Universitas Internasional Batam, 2023)
This paper is aimed at exploring the use of Glodon software using BIM in construction. The objective of this paper is to identify the satisfaction level of the Glodon software during the pre-contract stage of the construction project. A structured questionnaire was used to analyze Glodon software users. The result shows that the draw function, identify function, and import and export BIM model are satisfactory functions in the Glodon software during the pre-contract stage. The findings will give an understanding of the limitations and acceptability of the software in practice. The limitation of this study is that it was done in Klang Valley, Malaysia, and explored the tool satisfaction in the software.